2023
DOI: 10.3389/fcell.2023.1197226
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metabolism on the adaptation of organisms to environmental change

Abstract: Since Jacob and Monod’s discovery of the lac operon ∼1960, the explanations offered for most metabolic adaptations have been genetic. The focus has been on the adaptive changes in gene expression that occur, which are often referred to as “metabolic reprogramming.” The contributions metabolism makes to adaptation have been largely ignored. Here we point out that metabolic adaptations, including the associated changes in gene expression, are highly dependent on the metabolic state of an organism prior to the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…We sequenced the genomes of the four evolved strains and found that the gene crr encoding glucose-specific phosphotransferase enzyme IIA component (EIIA Glc ) was mutated in all evolved strains (SI Appendix Table S4), in line with the findings that in various microbes the deletion of the gene crr diminished glucose repression on other carbon sources (4749). In the presence of glucose, EIIA Glc is dephosphorylated which can inhibit transporters (50) and the genes involved in the catabolism of other carbon sources (51). By comparing the transcriptomics data between the strain Ev3 and the wildtype strain on the mixture of glucose and trehalose, we found many differentially expressed genes in the phosphotransferase system (SI Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We sequenced the genomes of the four evolved strains and found that the gene crr encoding glucose-specific phosphotransferase enzyme IIA component (EIIA Glc ) was mutated in all evolved strains (SI Appendix Table S4), in line with the findings that in various microbes the deletion of the gene crr diminished glucose repression on other carbon sources (4749). In the presence of glucose, EIIA Glc is dephosphorylated which can inhibit transporters (50) and the genes involved in the catabolism of other carbon sources (51). By comparing the transcriptomics data between the strain Ev3 and the wildtype strain on the mixture of glucose and trehalose, we found many differentially expressed genes in the phosphotransferase system (SI Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biological basis of the minimization of proteome reallocation is the high cost and slow adjustment of protein synthesis and degradation 40, 48, 49 that the cells should consider when adapting to rapid perturbations. Additionally, the minimization of proteome reallocation is in line with the findings of proteome reserves 50, 51 , i.e., the proteome is not fully optimized for the environmental condition where the cells are living, as a suboptimal proteome could reduce the cost and time of reallocation upon the adaption to a new condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation